Loss Aversion and Consumption Choice: Theory and Experimental Evidence - Heiko Karle; Georg Kirchsteiger; Martin Peitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper we analyze a consumer choice model with price uncertainty, loss aversion, and expectation-based reference points. The implications of this model are tested in an experiment in which participants have to make a consumption choice between two sandwiches. We make use of the fact that participants di er in their reported taste di erence between the two sandwiches and the degree of loss aversion which we measure separately. We find that more loss averse participants are more likely to opt for the cheaper sandwich provided that their reported taste di erence is below some threshold, confirming the model s predictions.
Keywords: C91; D01; D11; 330